Problematyka członkostwa w kasach oszczędnościowo-kredytowych w orzecznictwie Sądu Najwyższego w latach 2019–2022 - Skoczek, Jacek (PRAWO i WIĘŹ, 2023)
The article is an analysis of three judgments of the Supreme Court issued in the years 2019-2022 regarding the issue of membership in cooperative savings and credit unions. The first of these judgments concerns the liability of members for losses incurred in connection with the declared shares. The description of the current legal status is preceded by a short historical outline of the development of members additional liability. Lawsuits were initiated by the trustees of the bankruptcy estate of credit unions, who demanded additional payments from members for double liability despite the lack of a resolution of the general meeting on such a method of covering the loss. One of these proceedings ended with a request to the Supreme Court, which was answered by the Supreme Court in its judgment of 12 December 2019. Another membership issue dealt with by the Supreme Court is the issue of the obligation to cover the declared share of a member of a credit union and the consequences of its failure. This issue was also brought to the attention of the Supreme Court as a result of the actions of trustees of credit unions who, despite the lack of a legal basis and the obvious limitation of claims, tried to claim undue benefits from members. The Supreme Court, in a way, confirmed some of the theses from the judgment of 2019, indicating that a member of a cooperative fund is primarily a consumer and as such deserves increased protection. The third discussed issue is the issue of membership of credit unions in the National Association of Cooperative Savings and Credit Unions, which associates all credit unions in Poland. The ruling issued in this case was initiated by the action of the bankruptcy trustee of credit union, who stated that the declaration of bankruptcy is tantamount to termination of membership in the National Cooperative Savings and Credit Union. However, the Supreme Court indicated that as long as the legal existence of the credit union lasts, even in the course of bankruptcy proceedings, it remains a member of the National Cooperative Savings and Credit Union.